The Effect of Exposure to Pilkada News on Instagram Social Media @Beritabalimedia Against Political Participation of Beginner Voters in Badung Regency in the 2020 Pilkada - Ni Made Yunantari Dewi; Pawito; Ign. Agung Satyawan (Journal of Social Interactions and Humanities, 2022)
The 2020 Pilkada will be held simultaneously on December 9 to elect regional heads in 270 regions of Indonesia, one of which is the Province of Bali. Badung Regency is an area that has the highest voter participation rate reaching 84.62%. This study aims to see whether the exposure of Pilkada news on Instagram social media @ Beritabalimedia can affect the political participation of novice voters in Badung Regency. This research uses explanatory quantitative research method with Uses and Effects Theory . The data analysis technique used was simple linear regression analysis with the SPSS 18 program. The results showed that the exposure to the Pilkada news on Instagram @beritabalimedia social media had a positive influence on the political participation of novice voters in Badung Regency. When the news of the regional head election on Instagram @beritabalimedia increases, the political participation of novice voters in Badung Regency is also higher.